2009
DOI: 10.1002/joc.1916
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the skill and added value of a reanalysis‐driven regional simulation for Alpine temperature

Abstract: ABSTRACT:To determine whether the use of regional climate models improves the representation of climate is a crucial topic in climate modelling. An improvement over coarser scale models is expected especially in areas with complex orography or along coastlines. However, some studies have shown no clear added value for regional climate models. In this study a high-resolution regional climate simulation performed with REMO 5.0 (regional model) over the whole of Europe over the period 1958-1998 is analysed for 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
76
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 41 publications
7
76
0
Order By: Relevance
“…Thus, the added value in RCM simulations is commonly significant in regions with fine-scale surface forcing, whereas the performance of RCMs is less improved or even worse than that of the driving GCM over relatively flat regions. For instance, Prömmel and Geyer (Prömmel et al, 2010) also found that some RCMs show larger biases compared to their driving GCM in relatively flat regions surrounding the Alps, especially in summer. In most cases, the five RCMs perform better than the driving GCM HadGEM2-AO.…”
Section: The Added Values For Rcmsmentioning
confidence: 99%
“…Thus, the added value in RCM simulations is commonly significant in regions with fine-scale surface forcing, whereas the performance of RCMs is less improved or even worse than that of the driving GCM over relatively flat regions. For instance, Prömmel and Geyer (Prömmel et al, 2010) also found that some RCMs show larger biases compared to their driving GCM in relatively flat regions surrounding the Alps, especially in summer. In most cases, the five RCMs perform better than the driving GCM HadGEM2-AO.…”
Section: The Added Values For Rcmsmentioning
confidence: 99%
“…This implies that, from a practical viewpoint, the key issue in the nesting regional modelling technique evaluation is to determine whether RCM simulations improve the representation of climatic statistics compared to the driving data (Prömmel et al 2010). Generally, studies evaluating the relative skill of RCMs and the driving fields are designated as added value (AV) studies (Bärring and Laprise 2005;Rockel et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, however, the AV problem received increased attention and become the main subject of several studies (Castro et al 2005;Sotillo et al 2005;Duffy et al 2006;Feser 2006;Kanamitsu and Kanamaru 2007;Rauscher et al 2007;Sanchez-Gomez et al 2009;Winterfeldt and Weisse 2009;De Sales and Xue 2010;Prömmel et al 2010) and a central topic in a number of workshops (Bärring and Laprise 2005;Rockel et al 2010). Although some authors (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantages of RCMs over GCMs are increased resolution, more parsimony in terms of representing sub-grid-scale processes, and often improved modelling of spatial patterns, particularly in regions with coastlines and considerable topographic features (e.g. van der Linden and Mitchell, 2009;Prömmel et al, 2010;Feser et al, 2011). Current computing power is now allowing for ensembles of regional climate models to be performed, allowing for sampling of model structural uncertainty (Christensen et al, 2007;Giorgi and Bates, 1989;van der Linden and Mitchell, 2009;Mearns et al, 2013;Solman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%